Identification of coinfections by viral and bacterial pathogens in COVID-19 hospitalized patients in Peru: molecular diagnosis and clinical characteristics - Martins Luna, Johanna Elizabeth (2021)
The impact of respiratory coinfections in COVID-19 is still not well understood despite the growing evidence that consider coinfections greater than expected. A total of 295 patients older than 18 years of age, hospitalized with a confirmed diagnosis of moderate/severe pneumonia due to SARSCoV-2 infection (according to definitions established by the Ministry of Health of Peru) were enrolled during the study period. A coinfection with one or more respiratory pathogens was detected in 154 (52.2%) patients at hospital admission. The most common coinfections were Mycoplasma pneumoniae (28.1%), Chlamydia pneumoniae (8.8%) and with both bacteria (11.5%); followed by Adenovirus (1.7%), Mycoplasma pneumoniae/Adenovirus (0.7%), Chlamydia pneumoniae/Adenovirus (0.7%), RSVB/Chlamydia pneumoniae (0.3%) and Mycoplasma pneumoniae/Chlamydia pneumoniae/Adenovirus (0.3%). Expectoration was less frequent in coinfected individuals compared to non-coinfected (5.8% vs. 12.8%). Sepsis was more frequent among coinfected patients than non-coinfected individuals (33.1% vs. 20.6%) and 41% of the patients who received macrolides empirically were PCR-positive for Mycoplasma pneumoniae and Chlamydia pneumoniae.